Evaluating the Potential of Modified Mango Leaves as a Biosorbent for the Removal of Mercury (II) Ion and Congo Red from Wastewater - Oluwaseun Adekoya Adelaja; Babafemi Raphael Babaniyi (Sustainable Chemical Engineering, 2024)
The discharge of harmful metallic elements from industrial byproducts has resulted in notable environmental and public health risks. The aim of this study was to investigate the effectiveness of mango leaves as a cost-effective adsorbent in removing Hg (II) ions from industrial effluents. Experimental procedures were carried out under controlled conditions at ambient temperature to evaluate the influence of pH, contact duration, initial metal concentration, adsorbent dosage, and temperature on the adsorption mechanism. The most favorable pH for optimal Hg (II) ion adsorption was identified as pH 7. The adsorption process displayed swift kinetics in the initial 30 minutes of contact, leading to a removal rate exceeding 90%, with equilibrium achieved after 70 minutes of stirring. Kinetic analysis revealed a significant correlation coefficient for the pseudo-second-order kinetic model. The adsorption of Hg (II) ions escalated with increased stirring intensity and decreased adsorbent dosage. The interaction between Hg (II) ions, Congo red, and mango leaves was analyzed using Langmuir, Freundlich, and brunaer-emette-teller (BET) isotherm models. The equilibrium data was best fitted by the Langmuir model, presenting a correlation coefficient of 0.98 and a maximum adsorption capacity of 28.40 mg/g. These results underscore the potential of mango leaves as an affordable bio-adsorbent for addressing heavy metal pollution in wastewater.